Addiction to Sugar and Its Link to Health Morbidity - Yogarabindranath Swarna Nantha (SAGE Publishing, 2014)
Objectives: The average consumption of sugar in the Malaysian population has reached an alarming rate, exceeding the benchmark recommended by experts. This article argues the need of a paradigm shift in the management of sugar consumption in the country through evidence derived from addiction research. Methods: "Food addiction" could lead to high levels of sugar consumption. This probable link could accelerate the development of diabetes and obesity in the community. A total of 94 reports and studies that describe the importance of addiction theory-based interventions were found through a search on PubMed, Google Scholar, and Academic Search Complete. Results: Research in the field of addiction medicine has revealed the addictive potential of high levels of sugar intake. Preexisting health promotion strategies could benefit from the integration of the concept of sugar addiction. A targeted intervention could yield more positive results in health outcomes within the country. Conclusion: Current literature seems to support food environment changes, targeted health policies, and special consultation skills as cost-effective remedies to curb the rise of sugar-related health morbidities.